(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
pepper on serum biochemistry and hematological indices of broiler. One hundred and twenty (120) day old broiler chicks (Ross 308) were randomly divided into 4 treatment groups and 3 replicates of 10 birds per replicate in a completely randomized design. A mixture of cinnamon and red pepper at the ratio of 1:1was put in broiler diets at 0%, 0.5%, 1.0% and 1.5% at starter and finisher stages and were fed to broilers for 8 weeks. At the end of the experiment, 3 birds per replicate were selected and used for analyses of serum biochemistry and haematological indices. Results of serum biochemistry showed significant (P <0.05) effects of dietary cinnamon and red pepper inclusion on Cholesterol, aspartate aminotransferase, creatinine, urea, alkaline phosphatese, alanine aminotransferase, total protein, albumin, glucose, red blood cell count, white blood cell count, hemoglobin, packed cell volume, mean cell hemoglobin, neutrophils, platelet, mean cell volume and mean cell haemoglobin concentration. The results of the experiment showed that cholesterol and urea levels decreased as the level of cinnamon and red pepper increased but treatment three had the normal cholesterol level for broiler. Therefore, cinnamon and red pepper mixture should be included at 1.0% for optimum growth and performance of broiler birds.